Inclusive development in rural Indonesia: Actualizing disability rights in Lheu Eu Village - Mudhafar Anzari; M. Ikhwan; Syukriah Syukriah (Goodwood Publishing, 2024)
Purpose: This study addresses the marginalization of persons with disabilities in rural Indonesian villages, specifically examining the implementation of Law No. 8 of 2016 concerning Persons with Disabilities. This research seeks to enhance the status of persons with disabilities, ensuring equal rights and opportunities for their active participation in village development. Research methodology: This study employs a normative juridical methodology, analyzing data from legal documents and literature, complemented by an empirical approach through interviews with key stakeholders. This mixed-methods approach helps clarify the legal rights of persons with disabilities and gather insights into the perspectives of village governments on inclusion. Results: This study highlights the need for a community-centered development model that integrates the interests of persons with disabilities. This underscores the importance of adhering to human rights principles in ensuring the well-being of persons with disabilities in Lheu Eu Village, Darul Imarah District, and Aceh Besar. The study also emphasizes the necessity of collaborative efforts among village governments, businesses, academics, and disability advocates to implement legal mandates and regulatory frameworks for disability inclusion effectively. Limitations: The findings of this study are primarily based on qualitative data, which may not capture the full extent of the issues faced by people with disabilities in different rural contexts. Additionally, the research was limited to a specific geographic area, which may limit the generalizability of the results to other regions. Contribution: This study contributes to the body of knowledge on rural development and disability rights in Indonesia by providing a comprehensive analysis of the legal and social frameworks necessary for the inclusion of people with disabilities in village development. It offers practical recommendations to policymakers, village authorities, and other stakeholders to enhance the implementation of inclusive policies and practices.